Principles of Minimum Wage Policy - Economics, Institutions and Recommendations - Hansjörg Herr; Milka Kazandziska (International Labour Organization (ILO), 2011)
Minimum wage policy supported by a strong social policy is an efficient mechanism against poverty and income erosion of the poorest households. Minimum wage is one of the instruments which can control wage dispersion and in this way reduce income inequality. It can also help to prevent a general decline in the level of nominal wages and deflationary developments. For almost two decades now Japan has been suffering from deflationary tendencies triggered by falling nominal wages and unit-labour costs (Herr/Kazandziska 2010). There is a certain likelihood that the United States, Europe and other OECD countries will fall into a deflationary trap over the next decade, and a minimum wage policy could help to reduce this danger. The purpose of this paper is to discuss the principles of minimum wage policy whereby economic dimensions as well as institutional and political questions are taken into account. In the next section of the paper different theoretical views regarding the question of minimum wages are summarised. We concentrate on the neoclassical and Keynesian paradigm. Then institutional and political questions are discussed. Who sets the minimum wage, how is it determined, how frequently is it adjusted, which criteria are taken into account when deciding about the amount of the minimum wage, etc. Moreover, the connection to wage bargaining and the importance of minimum wages for unions are thoroughly examined.
Keywords: 330; minimum wage; low income; wage policy; Brazil; Cambodia; China; India; Iran; Islamic Republic; Malaysia; Namibia; Nigeria; Russian Federation; South Africa